Estimates Of Genetic Traits In Silkworm (Bombyx Mori L.) Under Temperate Conditions Of Kashmir (Applied Biological Research, 2015)
The genetic parameters, trait association and path coefficient analysis  between silkgland weight and its attributes of 10 silkworm genotypes  were studied during spring and summer seasons of 2010-11 at TSRI,  SKUAST-Kashmir (Mirgund). The genotypes exhibited wide range  variability for all the traits studied. High heritabilityaccompanied by  moderate to high genotypic coefficient of variation and genetic gain were  observed for filament length, shell ratio, single shell weight and filament  size. Correlation studies indicated that during spring season, silkgland  weight showed positive and significant correlation with shell ratio, while  it showed significantly negative association with silkgland somatic index,  while during summer season it showed significant positive association  with all the traits except silk conversion index. The silkgland attributes  exhibited varied magnitude of direct effects on silkgland weight during  both spring and summer season. During summer season single shell  weight showed the highest direct positive effect on silkgland weight  which was followed by the filament length, while during spring season,  highest positive direct effect on silkgland weight was exhibited by cocoon  shell percentage(3.574) and single shell weight (3.346).
Keywords: Bombyx mori; correlation; genetic advance; heritability; path coefficient analysis